Pelatihan Analisis Usaha, Penerapan Teknologi, Dan Digital Marketing Pada Usaha Mikro Pempek - Whetyningtyas, Aprilia; Faidah, Faridhatun; Nadia, Linda Putri (Unri Conference Series: Community Engagement, 2024)
Entrepreneurial development can improve the community's economy by opening new jobs and helping increase economic growth. Business actors must be adaptive to technology to increase their turnover. The partner of this service activity is the Pempek micro business "Hanif," located at Muria Indah Housing, Kudus Regency. Partners have not implemented financial recording management in running their business, such as not doing business analysis calculations. In its production activities, the pempek business "Hanif" still uses a manual machine to grind fish meat, so it still takes a long time to make pempek. In addition, the pempek "Hanif" business has been selling its products offline through resellers and depositing them at Joy and Chyntia Bakery in Kudus. This service activity aims to provide solutions by providing training in business analysis calculations, the application of meat grinder machine technology to increase production capacity and digital marketing training to maximize sales and products that the wider community can know. The output of this community service activity is an increase in partner empowerment, namely increasing partner knowledge related to business analysis, increasing the number and capacity of production, increasing the number of assets, increasing partner sales turnover, and improving partner skills in digital marketing.